Implementasi Dakwah dalam Menanamkan Nilai-nilai Pendidikan Islam untuk Membina Kepribadian Sehat - Dewi Sa’diyah (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2015)
This study shows that goals and method in order to build healthy character refer to vision and mission of Faculty of Da’wah and Communications. The Development of faitful individuals with beliefs in One Suprema God and healty personal characters and with the following indicators: proper religious teachings, good worship, healthy personality, good social skills, critical thinking, and active participation in organizing and developing religious activities at campus level. All those programs should be well managed, and this study has successfully constructed a implementation da’wah for students’ healthy character building at campus. The present study has made an important contribution to the vision and mission of Communications and Islam Broadcasting to create ulul albab human kind.